Neighbourhood transportation, elapsed years, and well-being after surrendering the driver's licence in older Japanese adults: The JAGES longitudinal study. (April 2023) - Yano, Masayo; Ichikawa, Masao; Hirai, Hiroshi; Ikai, Tomoki; Kondo, Naoki; Takagi, Daisuke
Highlights: We examined psychosocial changes after surrendering driver's licence in older adults. Elapsed years after surrender was considered to examine acute trend after transition. Social interactions with friends decreased within three years after surrendering. This trend was not moderated by the number of public transportations in neighbourhood. Abstract: This study aimed to examine how the associations between surrendering driving licence and changes in self-rated health and social interactions among older adults differ by the years elapsed since surrendering and the number of public transportation systems (PTS) in the neighbourhood. We used the 2013 and 2016 survey data from the Japan Gerontological Evaluation Study targeting residents aged ≥65 years in 30 municipalities in Japan. Two-waves longitudinal data from 4894 older adults were evaluated. Based on the difference-in-differences method, the interaction terms of respondents' driving status, which was the categorical exposure variable representing respondents' driving status for three years during the study period, and a dummy variable of year (2016) were used as explanatory variables in logistic regression analyses to examine changes in outcomes (poor self-rated health and infrequent meeting with friends) between 2013 and 2016 by driving status during this period. Analyses were stratified based on neighbourhood PTS ('more PTS' and 'fewer PTS' groups). We found that, while surrendering licence within three years was associated with increased probability of poor self-rated health in more PTS group, the confidence interval was large. Although surrendering licence within three years was associated with decreased social interactions, this association weakened if licence was surrendered more than three years ago. These associations were not markedly affected by neighbourhood PTS. Our findings suggested that, regardless of neighbourhood PTS, support and care to promote social interactions at or shortly after surrendering licence may be beneficial to the well-being of older adults who lost their driving licence.